Makaria e therapeia: bem-aventurança, espiritualidade e saúde integral - Sobral, Ricardo José Cavalcanti (2019)
The purpose of this research is to analyze the Beatitudes inserted by Jesus in the Sermon on the Mount, more specifically identified in the biblical text of the Gospel according to Matthew (Mt 5-7). The word Blessed is derived from the Greek term Makarioi - Mακάριοι in Greek. The term is translated as, happy, blessed, privileged recipient of divine favor or how blessed. From these meanings, it is understood that the appreciation of Jesus falls upon the poor in spirit, those who hunger and thirst for justice and the simple of heart. In short, the emphasis is given to what is fundamental, the human being. In this sense, we propose to investigate the Beatitudes, circumscribing their spiritual and therapeutic meaning during human suffering and difficulties in the search for wholistic health. Starting with challenging question: Does the Beatitudes, proposed by Jesus Christ, contain therapeutic elements that contribute to the human being finding ways of peace and spiritual health that he needs? We used the path of qualitative research method by way of discourse analysis, building the theoretical framework through the contributions of such authors as Jung (1963, 1964, 1982, 1983, 1989, 1991, 2002, 2003); Dethlefsen and Dahlke (1993); Csikszentmihalyi (1990); Bisquerra (2000); Stocker and Hegeman (2002). At the end of the research, we realized that it is possible to identify alternatives to achieve happiness and emotional well-being. The observations of the proposals of Jesus Christ, contained in the Beatitudes, linked to the concepts of emotions and their action in humanity, can lead us to the understanding that there are possibilities for the human being to reach a state of happiness, as well as to wholistic health, through their relationships with their affections, their satisfactions and their feelings to what life offers to them.